The AI Revolution in Arabic Language Learning: An Analysis of ChatGPTâ€™s Role in Autonomous Learning - Humairoh, Sitti Wardatul; Nurul Hadi; Umi Hanifah (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2026)
The rapid advancement of artificial intelligence (AI) has increasingly influenced language education, including Arabic as a foreign language. This study examines the role of ChatGPT as an AI-based conversational model in supporting autonomous Arabic language learning and explores the pedagogical implications of its use in the digital era. Employing a qualitative conceptual library research approach, the study synthesizes academic literature published between 2020 and 2025 on AI-assisted language learning, learner autonomy, and Arabic language pedagogy. This synthesis is complemented by structured interaction simulations with ChatGPT, which are employed as analytical artifacts. Through conceptual and thematic analysis, the study identifies three core pedagogical functions of ChatGPT: (1) providing interactive and adaptive linguistic input, (2) delivering corrective feedback, and (3) functioning as a co-writing partner that supports text revision. These functions enable flexible, iterative, and reflective language practice while maintaining learner control over the learning process. The findings suggest that the use of ChatGPT should be integrated within a well-defined pedagogical framework, underscoring the continued importance of human instructors and the need for further empirical research. This study proposes a conceptual framework that positions ChatGPT as a learning companion in Arabic language education.